Pyo-septic complications of severe necrotizing forms of acute pancreatitis - Veligotsky, N. N.; Arutyunov, S. E.; Klymenko, M. V.; Aleksanyan, K. A. (Modern medical technology, 2019)
Purpose of the study. Develop an algorithm for the diagnosis and treatment of purulent-septic complications of severe necrotizing forms of acute pancreatitis. Materials and methods. 5400 patients with acute pancreatitis were treated. To determine the infected pancreatic necrosis, the blood calcium level, and blood procalcitonin were studied, and a fine-needle biopsy was performed. Surgical interventions were performed in 874 (16,2%) patients who underwent 1057 surgical interventions. Results. 782 minimally invasive interventions were performed in 645 patients: video laparoscopic – 608 (77,7%), puncture-draining (under ultrasound control) – 102 (13,0%), endoscopic – 38 (4,9%). The following purulent-septic complications of severe forms of acute pancreatitis were revealed: infected pancreatic necrosis in 189 (17,9%), infected peripancreonecrosis in 167 (15,8%), infected pseudocystin109(12,5%)patients.173(19,8%) singlestage operative interventions were performed, 56 (6,4%) open-stage multistage patients were performed, and extended necrsequestrectomy was performed. Among minimally invasive interventions, minilaparotomy and lumbotomy were performed in 34 (4,3%). Conclusion. The use of monitoring laboratory and instrumental methods of research in the diagnosis of severe forms of acute pancreatitis and its complications allows you to determine in time the degree and volume of necrotic lesions of the pancreas and develop surgical tactics.